The international distribution of news the Associated Press, Press Association, and Reuters, 1848-1947 - Silberstein-Loeb, Jonathan 1981- (Cambridge studies in the emergence of global enterprise., 2014)
"Based on newly available and extensive archival evidence, this book traces the history of international news agencies and associations around the world from 1848 to 1947. Jonathan Silberstein-Loeb argues that newspaper publishers formed news associations and patronized news agencies to cut the costs of news collection and exclude competitors from gaining access to the news. In this way, cooperation facilitated the distribution of news. The extent to which state regulation permitted cooperation, or prohibited exclusivity, determined the benefit newspaper publishers derived from these organizations. This book revises our understanding of the operation and organization of the Associated Press, the BBC, the Press Association, Reuters, and the United Press. It also sheds light on the history of competition policy respecting the press, intellectual property, and the regulation of telecommunications"-- Provided by publisher.